PENERAPAN MEDIA BONEKA TANGAN UNTUK MENINGKATKAN KERETAMPILAN BERCERITA SANTRI - Desty Pratiwi; Abdurrahmansyah Abdurrahmansyah; Sukirman Sukirman (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2019)
Hand puppet media is a way to improve Santri's storytelling skills. What is seen from the first problem What is the skill of storytelling of the control class santri that does not use puppet media. Second What is the skill of storytelling of students in the experimental class using hand puppet media. This research is a quantitative study, the data collection techniques in this study used the method of test observation and documentation, to analyze the data using the TSR test. The data of this study were collected from the number of students of class III Ibtidaiyah Indralaya Madrasah taken as much as 20% of the total number of santri namely as many as 132 students and obtained 50 respondents, starting from class III A and class III CBased on the results obtained from the field and calculations using the TSR Test, it can be concluded that: firstly the control skills of the students in the control class in the high categorized learning process were 3 santri (18.52%.) And the moderate categorized values ​​were 8 santri (59.26%) As for the low categorized values ​​as many as 16 santri (22.22%) as for the two experimental students' storytelling skills in the learning process it was categorized as high as 5 santri (21.7%) and medium ones as many as 14 santri (60.8%) and categorized low as many as 4 santri (17.39%),. To find out how the difference is using the rXY formula. from the results of the XY count, it proves that the results of r count are greater than r table both at the significant level of 5% and 1% (20.1 <4.69> 2.68). This shows that